Lichen striatus. An inflammatory disease occurring on a clinically silent nevus. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2003)
We know many disorders distributed according to the Blaschko lines, thanks to the relevant reports of Rudy Happle and many other Authors. How-ever, many problems are still open to discussion and some of them have significant clinical implications. An interesting problem regards the clinically silent nevus (3), namely a nevus condition that is clinically invisible until when it is unveiled by an exogenous agent. This concept is necessary to understand the numerous acquired diseases distributed according to the Blaschko lines. Some of these disorders such as lichen striatus and blaschkitis exist only in a segmentary form, whereas others such as fixed drug eruption, lichen ruber planus, lichen sclerosus, lichen nitidus, lupus erythematosus, psoriasis, pemphigus, lichenoid eruptions and vitiligo usually affect the entire skin surface, but sometimes may exist in a segmentary form and thus be distributed according to the Blaschko lines. In the latter case there are two possibilities as follows: the skin disease affects only a cutaneous segment or, alternatively, the skin disease bilaterally affects a more or less large skin surface, but it is more marked in one segment. All these acquired skin disorders can be explained by the existence from the fetal life in one cutaneous segment of a clone of mutated cells. The mutation consists in a predisposition of the cell to display pathological manifestations when coming into contact with a triggering factor (...).